Detection of EGFR Mutations in Cerebrospinal Fluid of EGFR-Mutant Lung Adenocarcinoma With Brain Metastases - Shi, Liang; Tang, Junfang; Tao, Hong; Guo, Lili; Wu, Weihua; Wu, Hongbo; Liu, Zichen; Tong, Li; Wu, Wei; Li, Hongxia; Meng, Qiyi; Xu, Liyan; et al. (Frontiers in Oncology, 2021)
Background: We aimed to investigate the feasibility of detecting epidermal growth factor receptor (EGFR) mutations in cell-free DNA (cfDNA) from cerebrospinal fluid (CSF) and plasma of advanced lung adenocarcinoma (LADC) with brain metastases (BMs) by droplet digital polymerase chain reaction (ddPCR). Methods: Thirty advanced LADC patients with BMs were enrolled, and their matched CSF and plasma samples were collected. Droplet digital PCR was used to test cfDNA in CSF and plasma for EGFR mutation status. The clinical response and prognosis were evaluated. Results: Out of 30 patients, there were 21 females and 9 males, aged 34-75 years. In all of cases, CSF cytology were negative. In ddPCR assays, 10 patients (33.3%) had EGFR mutation in CSF, including 3 cases of EGFR T790M mutation, and 16 patients (53.3%) had EGFR T790M mutation in plasma, including 6 cases of EGFR-T790M mutation. Five patients with activating EGFR mutations in CSF achieved intracranial partial response (iPR) after combination treatment with the first-generation EGFR-tyrosine kinase inhibitors . Three patients with EGFR T790M mutations in CSF achieved iPR after second-line osimertinib treatment. The median overall survival and intracranial progression-free survival were 17.0 months and 11.0 months, respectively. Conclusion: It was feasible to test EGFR mutation in cerebrospinal fluid and plasma. In LADC patients with brain metastasis, cerebrospinal fluid can be served as a liquid biopsy specimen to guide the treatment strategy by monitoring EGFR mutation status.